Women's political role and poverty in the educational dimension: a district-level anlysis in India - Francesco Burchi (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
This paper contributes to the debate on the effects of women's political representation. It has a threefold objective: (1) to analyse whether the gender of elected politicians is relevant to the educational achievements of residents of the Indian districts in which they were elected; (2) to test whether politicians are more sensitive to the needs of people of the same gender; (3) to explore the possible channels through which these relationships operate. By applying instrumental variable regressions to a data set obtained by merging individual data with district-level political variables, we concluded that a 10% increase in women's political representation at district level may produce a 5.9% increase in the probability of children completing primary school. In a further analysis, we found a striking difference in the results when broken down by gender: women's political agency affects the education of a significantly larger number of girls than boys. Finally, none of the channels we examined relating to school buildings and the coverage of the Mid-Day Meal scheme helped explain the above relationship. This is due in part to poor-quality data. In conclusion, these findings provide further evidence of the benefits of women's political representation and should be taken into consideration in the current debate on the Women's Reservation Bill in India.
Keywords: 330